Degummed Pongamia oil – Ethanol microemulsions as novel alternative CI engine fuels for remote Small Island Developing States: Preparation, characterization, engine performance and emissions characteristics. (May 2020) - Prasad, Salvin S.; Singh, Anirudh; Prasad, Surendra
Abstract: Diminishing fossil fuel reserves, rising market price for diesel and the need to combat greenhouse gas emissions have led to the development of a crucial area of research into alternative fuels for diesel engines. In this work, a hybrid fuel was prepared for the first time by blending Pongamia oil, hydrated ethanol (95% purity) and butanol (as a surfactant). To eliminate engine modification and reduce injector clogging in the diesel engine, degummed Pongamia oil was utilized for preparing hybrid fuels. The results show that the density and viscosity of Pongamia oil reduced considerably after blending with ethanol and was brought closer to that of diesel. The gross calorific values were comparable with that of diesel. The brake thermal efficiencies of using hybrid fuels on a compression ignition engine were very similar to that of diesel. The emissions characteristics of hybrid fuels show reduced emissions of CO2, NOx and SO2 . The hybrid fuel blends E22 B27 DPO51  and E17 B16 DPO67 prepared with degummed Pongamia oil show the lowest emissions. Thus, these hybrid fuels have the potential to substitute diesel to run diesel powered inter-island shipping vessels, fishing boats and smaller power plants for household electricity in remote and outer islands of developing countries. Highlights: Degummed Pongamia – ethanol hybrid fuels have the potential to replace diesel fuel. The fuel characteristics of most suitable blends are closer to that of diesel. Brake thermal efficiencies of hybrid fuels are comparable to that of diesel. Emissions characteristics of hybrid fuel show reduced emissions of CO2, NOx and SO2 .